139 Primary Seminal Vesicle Carcinoma: A Case Report. (11th January 2018) - Coldren, Daniel; Kertowidjojo, Elizabeth; Waltzer, Wayne; Liu, Jingxuan
Abstract: Primary seminal vesicle carcinoma (SVC) is an extremely rare and poorly understood entity that maintains a poor prognosis. We present a case of a 31-year-old man with history of chronic prostatitis, presenting with three years of worsening hematospermia and pain. A computed tomography (CT) scan in 2013 revealed enlargement of the right seminal vesicle (3.7 cm) with stranding, suspicious for an infectious process. Magnetic resonance imaging (MRI) obtained in 2016 revealed a heterogeneously enhancing solid mass in the right seminal vesicle, measuring 8.1 cm. The mass was resected, and histologic evaluation revealed a poorly differentiated adenocarcinoma with necrosis and hemorrhage. In order to exclude metastasis from another site, extensive immunohistochemistry and special stains were performed to reveal tumor cells positive for AE1/AE3, CAM5.2, CK903, PAX8, vimentin, Alcian blue, mucicarmine, keratin 7, and CA125; focally positive for inhibin, ER, and HNF1 beta; and negative for CK20, monoclonal CEA, S100, HMB45, Melan A, SMA, desmin, myogenin, WT-1, calretinin, chromogranin, synaptophysin, PSA, PSAP, p63, GATA3, PR, and CD34. Post-procedural MRI and positron emission tomography (PET) scan revealed no residual disease or any other suspicious focus. The patient is currently undergoing multimodal therapy with radiation and multi-drug chemotherapy. Due to the rarity of this tumor, to date, no guideline for the grading or pathologic staging of this tumor is available. This case report serves to further characterize the clinical presentation, appearance, and immunoprofile of SVCs.